Rancang Bangun Aplikasi Penjurusan Minat Bakat Menggunakan Metode Forward Chaining - Levi Jordan Halim; Ranny Ranny; P.M. Winarno (Ultimatics : Jurnal Teknik Informatika, 2015)
Plentiful choices of Student Activities Unit that offered by a campus like Multimedia Nusantara University can help students who want to choose a unit that suitable for them. The decision support system application with Forward Chaining method is built to help students choosing the Student Activity Unit that suits them. Multiple Intelligence method is used as the knowledge base at making the rules. The aspects that considered as attributes to choosing the Student Activities Unit is the initial interest and also the multiple intelligence scores that the level of conformity will be searched by using Forward Chaining method. This research has produced a knowledge-based decision support system that can help students at choosing Student Activities Unit that suitable for them with the highest accuracy of 86.67 percent. This system is designed in website with PHP and MySQL database programming language. Index Terms—Forward Chaining, Knowledge-based, Multimedia Nusantara University, Multiple Intelligence, Student Activities Unit